Community-Based Whale Sharks Conservation to Strengthen Ma-rine Tourism Management in Sumbawa - Nurul Amri Komarudin; Fahrunnisa Fahrunnisa; Yuni Yolanda (International Journal of Geotourism Science and Development, 2022)
Sumbawa is famous for its marine tourism, apart from the beauty of its beaches, Sumbawa also has marine fauna that attracts the attention of tourists, namely whale sharks. It is recorded that there are around 99 species of Whale Sharks located in Saleh Bay, Sumbawa. Thus, making Saleh Bay the location with the second largest whale shark population in Indonesia and UNESCO designated Saleh Bay as part of the SAMOTA biosphere reserve. Currently, whale sharks have protected fauna according to the decree of the Minister of Marine Affairs and Fisheries No. 18 of 2013. This is due to the pollution of whale shark habitats by pollutants including garbage and microplastics. In addition, the Overexploitation of whale sharks is some of the causes of the significant decline in whale shark populations. Marine ecotourism activities in the form of exhibiting Whale Sharks to tourists can be an alternative way of sustainable use because it has minimal impact on individual Whale Sharks, in addition, marine ecotourism activities can also provide economic benefits to the Sumbawa community and regional development including supporting efforts to protect and preserve the whale shark fauna. The Study "Community-Based Whale Shark Conservation to Strengthen Marine Tourism Management in Sumbawa “aims to present a blue economy model for coastal communities in Sumbawa and increase community participation in conservation activities, as well as improve the welfare of coastal communities in Sumbawa.